2015
DOI: 10.2340/16501977-1930
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive impairment after stroke: A systematic review of psychometric properties and clinical utility

Abstract: The MoCA is the most valid and clinically feasible screening tool to identify stroke survivors with a wide range of cognitive impairments who warrant further assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 59 publications
2
117
1
6
Order By: Relevance
“…The Montreal Cognitive Assessment (MoCA) is a recommended tool for assessing cognitive functions in patients with acute stroke (3, 4). Good validity and reliability were reported for those with mild to moderate stroke (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Montreal Cognitive Assessment (MoCA) is a recommended tool for assessing cognitive functions in patients with acute stroke (3, 4). Good validity and reliability were reported for those with mild to moderate stroke (4).…”
Section: Introductionmentioning
confidence: 99%
“…Good validity and reliability were reported for those with mild to moderate stroke (4). Studies performed on a subacute stroke population showed a positive association between impaired cognitive function assessed with the MoCA and a high level of global disability (5).…”
Section: Introductionmentioning
confidence: 99%
“…The MoCA has good psychometric properties and is a valid screening tool to detect post-stroke cognitive impairment [13]. Although a recent study [14] questioned the accuracy of the MoCA to assess attention and executive function by stroke lateralization, the majority of studies have shown the MoCA to be superior compared to other screening measures such as the MMSE [11, 15, 16].…”
Section: Assessmentmentioning
confidence: 99%
“…13 According to recent reviews, the MoCA is the most sensitive screening tool in detecting poststroke cognitive impairment without a ceiling effect. [14][15][16] To date, there are only a few studies that used the MoCA to assess changes in cognitive performance at repeated time points after stroke. [17][18][19] Two studies showed that MoCA scores improved in transient ischemic attack and stroke patients from baseline until 3-month follow-up.…”
mentioning
confidence: 99%